Pengaruh Citra Produk Dan Periklanan Terhadap Keputusan Pembelian Jahe Wangi CV. INTRAFOOD - Hidayat, Murshid; Istiyanto, Budi (Graduasi: Jurnal Bisnis & Ekonomi, 2012)
Seeing the development of business growth beverage products Ginger: Jahe Mantap, Jahe Wangi Sido Muncul, Jahe Merah, and other products that bervarian ginger, competing to market their products. In order to attract buyers will require a good brand image and advertising heavily. Formulation of the problem in this study: 1) Is there any effect on the product image and advertising on purchase decisions? And 2) Which are the most dominant among the product image and advertising on purchase decisions?. The purpose of this study: 1) To determine the influence of advertising and the image of the product on purchase decision, and 2) to determine which is the most dominant among advertising and product image on purchase decisions.,The hypothesis is: 1) product image positive influence consumer purchasing decisions, 2) Advertising positive influence on consumer purchasing decisions; 3) Advertising has the most dominant effect influencing purchase decisions of fragrant ginger CV. Intrafood.Alat analysis used in the study were: Validity, reliability testing, regression analysis, t test, F test, and R2 The conclusion of this study were: 1) There is a positive and significant correlation between the image of the product on purchase decision fragrant ginger CV. Intrafood, 2) There is a positive and significant correlation between advertising on purchase decisions fragrant ginger CV. Intrafood; 3) There is a positive and significant correlation between the product image and advertising on purchase decisions fragrant ginger CV. Intrafood; 4) Advertising is the dominant factor affecting the purchase decision fragrant ginger CV. Intrafood. Based on the conclusion, it can be suggested that the company is expected to continue to maintain and enhance the advertising strategy is to intensify the advertisements in the electronic media and print media are very easily spread. For the image of the companys products is expected to improve the image of the product by improving quality and providing packaging and price that makes consumers interested to buy it.